2017
DOI: 10.1039/c7nr05189a
|View full text |Cite
|
Sign up to set email alerts
|

Electrically and thermally conductive underwater acoustically absorptive graphene/rubber nanocomposites for multifunctional applications

Abstract: Graphene is ideal filler in nanocomposites due to its unique mechanical, electrical and thermal properties. However, it is challenging to uniformly distribute the large fraction of graphene fillers into a polymer matrix because graphene is not easily functionalized. We report a novel method to introduce a large fraction of graphene into a styrene-butadiene rubber (SBR) matrix. The obtained graphene/rubber nanocomposites were mechanically enhanced, acoustically absorptive under water, and electrically and therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…Due to the limited amount of GO in our composites, the thermal stability of the GO/SBR composites is not affected. The result is similar to those of GE/SBR 22 nanocomposites and GO/NR nanocomposites. 28 The residual amounts at 700 °C are 7.1, 10.7, 11.4, 12.4, and 15.4%, which are well correlated with the GO filler content.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Due to the limited amount of GO in our composites, the thermal stability of the GO/SBR composites is not affected. The result is similar to those of GE/SBR 22 nanocomposites and GO/NR nanocomposites. 28 The residual amounts at 700 °C are 7.1, 10.7, 11.4, 12.4, and 15.4%, which are well correlated with the GO filler content.…”
Section: Resultssupporting
confidence: 84%
“…The results further confirm that GO and SBR are successfully fabricated into the composite. 22 Furthermore, the Raman spectroscopy of the structural integrity of GO/SBR films was also performed. Due to its amorphous structure, SBR shows two small wide bands near 1000 and 2910 cm –1 , corresponding to symmetric ring breathing and CH 2 asymmetric stretching, 23 , 24 respectively, as illustrated in Figure 3 c. After introducing GO, two conspicuous characteristic peaks near 1347 and 1585 cm –1 correspond to the D (defects and disorder) and G (graphitic) bands of GO, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum EMI SE T value of the CNT/GNP/EUG composite is seen to be as high as ~42 dB, a value that meets the EMI shielding requirement for commercial products. Table 1 compares the results obtained in this work with other EMI shielding polymeric composites reported in previous work [17,18,20,28,[30][31][32]; it is seen that the CNT/GNP/EUG composites created in this work exhibit superior EMI SE T compared with previously studied composites. The results indicate that this work provides a practical and effective method for the preparation of high-performance EUG-based EMI shielding composites.…”
Section: Electrical Conductivity and Emi Shielding Properties Of The ...mentioning
confidence: 54%
“…[30] In addition, the embedded air voids or existing microbubbles are squeezed or closed under high deformation, so nanocomposites were found that the absorption peak shifted to high frequency or decrease significantly. [19,42,43] Also, as materials become highly compressed and deformed under the high hydrostatic pressure condition, the structure of polymer molecule chains is changed, and the movement between the nanofillers and polymer molecule chains in the matrix structure becomes more restricted. [44,45] Subsequently, materials' damping and underwater sound absorption property degrade for applications under high pressure.…”
Section: Mechanism Of Maintaining Underwater Sound Absorption At High Pressurementioning
confidence: 99%
“…[18] The optimal sound absorption coefficient of the nanocomposites was achieved as the graphene nanoplatelets (GNPs) content was 10 phr, and the average sound absorption coefficient was improved from 0.35 to 0.73 -an increase of nearly onefold. Further, Li et al [19] found that GNPs nanocomposites can maintain good underwater sound absorption performance at high hydrostatic pressure. The sound energies were dissipated by sliding of CNTs and GNPs and friction with the polymer matrix, so acoustic energies were transferred to thermal energies.…”
Section: Introductionmentioning
confidence: 99%